Crisis leadership and public governance during the COVID-19 pandemic international comparisons - Cheung, Anthony B. L. (Anthony Bing-leung) 1952-; Thiel, Sandra van (Critical perspectives and issues in governance and public management, 2023)
This book explores various issues and challenges emanating from the COVID-19 pandemic. It examines how governments worldwide have dealt with the pandemic. Post-COVID-19 and its disruptive impact on social and economic life as well as public and political attitudes, the world is not the same. A new normal has dawned in public management and public services, with immense implications. This volume collects the lessons drawn from the pandemic, notably how crisis leadership and public governance were used to combat the crisis, as well as which aspects were helpful in that regard.